TISSUE ORGANIZATION OF MUCOSAL IMMUNE RESPONSES: A COMPARATIVE HISTOLOGICAL ANALYSIS OF THE RESPIRATORY AND INTESTINAL BARRIERS - Alrudhan, Qays Hameed Abed (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Mucosal surfaces serve as critical defensive barriers that safeguard the organism from external environmental fluctuations and persistent pathogen threats. In response to these challenges, a specialized mucosal immune system has developed, which adapts through a process known as homing, allowing it to integrate with various tissues. This integrated immune system is responsible for producing, evaluating, and executing adaptive immune responses by establishing diverse immune microenvironments at mucosal locations. The present analysis centers on the similarities between the respiratory and intestinal mucosal systems, facilitating a comparative exploration of how a seemingly analogous system has evolved to fulfill the unique demands of different environments while preserving a robust foundational architecture. Method: Each mucosal microenvironment possesses distinctive features concerning its cellular composition, structural organization, and immune processes. To elucidate this well-characterized system, an examination of the invariant structural framework of these tissues will be conducted on both micro- and macro-scales, with an emphasis on the anatomy and cellular components of Peyer's patches (PP), bronchus-associated lymphoid tissue (BALT), conjunctiva-associated lymphoid tissue (CALT), tonsils, and isolated lymphoid tissues (ILT), along with smaller clusters found within the lungs. Result: Despite these specificities that may mitigate cross-competition among them, there is a proposition that the components of mucosa-associated lymphoid tissue (MALT) share evolutionary origins. A comparative analysis of the steady state microenvironments will delve into the complexities of immune engagement, the structural plasticity that facilitates intratissular memory, and the efficacy of effector responses that enable rapid pathogen clearance without incurring detrimental effects. Dendritic cells (DCs) residing in these environments play a pivotal role by capturing antigens utilizing various internalization receptorial setups and signal transduction pathways. The cross-presenting CD103+ DCs present in both mucosal systems influence the polarization of immune responses and the selection of immune strategies employed. Novelty: Finally, a succinct overview of the enhancing environments will be provided, addressing the proactive approaches adopted by pathogens and commensals, alongside the counterstrategies implemented by the immune system to address these threats. Special attention will be afforded to the collaborative roles of epithelial and immune cells in responding to viral infections and bacterial toxins.